Clean hydrogen for mobility – Quo vadis?. (1st June 2022) - Ravi, Sai Sudharshan; Aziz, Muhammad
Abstract: Achieving complete combustion of fossil fuels has long been thought of as a sufficient remedy for tackling vehicular emissions and the ensuing environmental effects. However, thanks to the increasing awareness around the climate change, the global dialogue has now shifted to realizing a carbon-free economy, which has set stricter curbs on the energy source that can power the future mobility. Therefore, the idea of "clean combustion" requires rethinking. Of the many choices for alternative clean fuels that are both energy-efficient and environment-friendly, hydrogen has always been eyed as the best clean alternative there is. This article reviews various available approaches to utilizing hydrogen for mobility applications with a discussion of their relative merits and shortcomings. In addition to well-discussed methods like fuel cell electric vehicles, hydrogen-based IC engines, and dual-fuel operation with hydrogen, this review also assesses the technical and economic feasibilities of using hydrogen in e-fuels and their implications for our existing infrastructure and future energy demands. Highlights: Feasibility of current H2 technologies for mobility is reviewed. Potential of e-fuels as hydrogen carriers to fuel the mobility sector is highlighted. Global strategies and policies enabling a hydrogen economy are outlined. Status quo of global hydrogen infrastructure for mobility and storage is discussed.